Ginsenoside Rg1 Exerts Anti-inflammatory Effects via G Protein-Coupled Estrogen Receptor in Lipopolysaccharide-Induced Microglia Activation - Gao, Xian-Qi; Du, Zhong-Rui; Yuan, Liang-Jie; Zhang, Wen-Di; Chen, Lei; Teng, Ji-Jun; Wong, Man-Sau; Xie, Jun-Xia; Chen, Wen-Fang (Frontiers in Neuroscience, 2019)
Abstract Neuroinflammation plays a pivotal role in the pathogenesis of Parkinson’s disease. Ginsenoside Rg1, the most active ingredient of ginseng, has been reported to exert neuroprotective effects via estrogen and glucocorticoid receptors. The present study evaluated the involvement of the G-protein-coupled estrogen receptor (GPER) in the anti-inflammatory effects of ginsenoside Rg1 against lipopolysaccharide (LPS)-induced microglia activation in the BV2 microglial cell line and ventral mesencephalic primary microglial culture. The pharmacological blockade and lentivirus-mediated siRNA knockdown of GPER were used to study the underlying mechanism. Rg1 attenuated LPS-induced up-regulation of TNF-α, IL-1β, iNOS, and COX-2 mRNA and protein levels. The GPER antagonist G15 blocked the inhibitory effects of Rg1 and the GPER-specific agonist G1 on LPS-induced microglia activation. Rg1 mimicked the effects of G1 by inhibiting the LPS-induced activation of NF-κB and MAPKs signaling pathways, which was also blocked by G15. Moreover, lentivirus-mediated small interfering RNA knockdown of GPER inhibited the anti-inflammatory effects of Rg1. Taken together, our results indicate that GPER is involved in the anti-inflammatory effects of Rg1 against LPS-induced microglia activation. These findings provide a new biological target of Rg1 for the treatment of neuroinflammatory disorders.